Overexpression of the 18 kDa translocator protein (TSPO) in the hippocampal dentate gyrus produced anxiolytic and antidepressant-like behavioural effects. (October 2017) - Li, Lei; Wang, Wei; Zhang, Li-Ming; Jiang, Xiang-Yun; Sun, Shu-Zheng; Sun, Li-Jun; Guo, Ying; Gong, Jie; Zhang, You-Zhi; Wang, Heng-Lin; Li, Yun-Feng
Abstract: The 18 kDa translocator protein (TSPO) is a five transmembrane domain protein that plays a crucial role in neurosteroid (e.g., allopregnanolone) synthesis by promoting the transport of cholesterol to the inner mitochondrial membrane. This protein is predominantly expressed in steroid-synthesizing tissues, including the central and peripheral nervous system, affecting stress-related disorders such as anxiety and depression. Recent studies have focused on the hippocampal dentate gyrus, which is very important for involvement of anxiety and depression. However, the exact role that TSPO plays in the pathophysiology of anxiety and depression and the involvement of the hippocampal dentate gyrus in regulating these behavioural effects remain elusive. This study used the lentiviral vectors mediating TPSO overexpression to assess the effects of TPSO overexpression in the hippocampal dentate gyrus on anxiolytic and antidepressant-like behavioural effects in mice. The expression of TSPO and the concentration of allopregnanolone in hippocampus tissues (3 mm in diameter around the injection site on both sides) were measured by Western blot and ELISA, respectively. The results indicated that microinjection of the LV-TSPO resulted in a significant increase in TSPO expression and allopregnanolone concentration in the hippocampus. Moreover, TSPO overexpression of the mouse hippocampal dentate gyrus generated significant anxiolytic and antidepressant-like behavioural effects in a series of behavioural models. These effects were completely blocked by the TSPO antagonist PK11195 (3 mg/kg, intraperitoneally) and the 5α-reductase inhibitor finasteride (5 mg/kg, intraperitoneally). Meanwhile, the increased allopregnanolone was also reversed by PK11195 and finasteride. In addition, neither PK11195 nor finasteride had an effect on the expression of TSPO. Overall, our results are the first to suggest that the overexpression of TSPO in the hippocampal dentate gyrus produced anxiolytic and antidepressant-like behavioural effects that are partially mediated by downstream allopregnanolone biosynthesis. Our results suggest that TSPO would be a potential anxiolytic and antidepressant therapeutic target. Highlights: Translocator protein 18 kDa (TSPO) is a therapeutic target for anxiety and neurologic disorders. Microinjection of the dentate gyrus with lentiviral vectors, which resulted in a significant increase in TSPO expression. TSPO overexpression of the mice hippocampal dentate gyrus generated anxiolytic and antidepressant-like behavioural effects. The effects were completely blocked by the TSPO antagonist PK11195 and the 5α-reductase inhibitor finasteride.